Exploration of Spirituality in Islamic Education: Perspectives on Gender Equality and Minority Rights - Januar, Januar; Rahmi, Alfi (HUMANISMA : Journal of Gender Studies, 2024)
This research aims to explore the exploration of spirituality, gender equality, minority rights in the context of Islamic education, and the integration of spirituality. This research uses a qualitative approach, and data collection techniques, namely interviews and document analysis. Qualitative data was analyzed using a thematic analysis approach by triangulating the data to increase validity. The research results show that the role of spirituality in education is the main pillar in forming a holistic individual. The integration of spiritual values in the curriculum forms students who are academically intelligent and morally responsible. Spirituality gives rise to empathy, tolerance, and justice, forming the basis of positive character. Spirituality-based Islamic education guides students to understand themselves and their environment in depth. Gender equality challenges involve unequal access and gender-based violence. Women's involvement in decision-making needs to be increased. Public awareness and policy support are key to creating a just society. Gender equality initiatives in Islamic education emphasize equal access and the development of social skills. Identification of minority rights demands recognition of language, culture, and protection of fundamental rights. Steps towards inclusive education include awareness, policy changes, human resource development, parental involvement, and continuous evaluation. The integration of spirituality, gender equality, and minority rights creates an inclusive and holistic system, empowering all learners. Penelitian ini bertujuan untuk mengetahui eksplorasi spiritualitas, kesetaraan gender, hak minoritas dalam konteks pendidikan Islam, dan integrasi spiritualitas. Penelitian ini menggunakan pendekatan kualitatif, teknik pengumpulan data, yaitu wawancara dan analisis dokumen. Data kualitatif dianalisis menggunakan pendekatan analisis tematik dengan melakukan triangulasi data untuk meningkatkan validitas. Hasil penelitian menunjukan bahwa Peran spiritualitas dalam pendidikan menjadi pilar utama membentuk individu holistik. Integrasi nilai-nilai spiritual dalam kurikulum membentuk siswa cerdas secara akademis dan bertanggung jawab moral. Spiritualitas memunculkan empati, toleransi, dan keadilan, membentuk dasar karakter positif. Pendidikan Islam berbasis spiritualitas memandu siswa memahami diri dan lingkungan secara mendalam. Tantangan kesetaraan gender melibatkan ketidaksetaraan akses dan kekerasan berbasis gender. Keterlibatan perempuan dalam pengambilan keputusan perlu ditingkatkan. Kesadaran masyarakat dan dukungan kebijakan kunci dalam menciptakan masyarakat adil. Inisiatif kesetaraan gender dalam pendidikan Islam menekankan akses setara dan pengembangan keterampilan sosial. Identifikasi hak minoritas menuntut pengakuan bahasa, budaya, dan perlindungan hak fundamental. Langkah menuju pendidikan inklusif mencakup kesadaran, perubahan kebijakan, pengembangan sumber daya manusia, keterlibatan orang tua, dan evaluasi terus-menerus. Integrasi spiritualitas, kesetaraan gender, dan hak minoritas menciptakan sistem inklusif dan holistik, memberdayakan semua peserta didik.